Annexin A1 Induces Skeletal Muscle Cell Migration Acting through Formyl Peptide Receptors - Bizzarro, Valentina; Belvedere, Raffaella; Dal Piaz, Fabrizio; Parente, Luca; Petrella, Antonello (PLOS ONE, 2012)
Annexin A1 (ANXA1, lipocortin-1) is a glucocorticoid-regulated 37-kDa protein, so called since its main property is to bind (i.e. to annex) to cellular membranes in a Ca2+-dependent manner. Although ANXA1 has predominantly been studied in the context of immune responses and cancer, the protein can affect a larger variety of biological phenomena, including cell proliferation and migration. Our previous results show that endogenous ANXA1 positively modulates myoblast cell differentiation by promoting migration of satellite cells and, consequently, skeletal muscle differentiation. In this work, we have evaluated the hypothesis that ANXA1 is able to exert effects on myoblast cell migration acting through formyl peptide receptors (FPRs) following changes in its subcellular localization as in other cell types and tissues. The analysis of the subcellular localization of ANXA1 in C2C12 myoblasts during myogenic differentiation showed an interesting increase of extracellular ANXA1 starting from the initial phases of skeletal muscle cell differentiation. The investigation of intracellular Ca2+ perturbation following exogenous administration of the ANXA1 N-terminal derived peptide Ac2-26 established the engagement of the FPRs which expression in C2C12 cells was assessed by qualitative PCR. Wound healing assay experiments showed that Ac2-26 peptide is able to increase migration of C2C12 skeletal muscle cells and to induce cell surface translocation and secretion of ANXA1. Our results suggest a role for ANXA1 as a highly versatile component in the signaling chains triggered by the proper calcium perturbation that takes place during active migration and differentiation or membrane repair since the protein is strongly redistributed onto the plasma membranes after an rapid increase of intracellular levels of Ca2+. These properties indicate that ANXA1 may be involved in a novel repair mechanism for skeletal muscle and may have therapeutic implications with respect to the development of ANXA1 mimetics.